2008
DOI: 10.1128/iai.01126-07
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae Surface Protein PcpA Elicits Protection against Lung Infection and Fatal Sepsis

Abstract: Previous studies have suggested that pneumococcal choline binding protein A (PcpA) is important for the full virulence of Streptococcus pneumoniae, and its amino acid sequence suggests that it may play a role in cellular adherence. PcpA is under the control of a manganese-dependent regulator and is only expressed at low manganese concentrations, similar to those found in the blood and lungs. PcpA expression is repressed under high manganese concentrations, similar to those found in secretions. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
96
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 64 publications
4
96
1
Order By: Relevance
“…PcpA is under the control of a manganese (Mn)-dependent regulator, PsaR, and the Mn concentration in the NP of mice has been shown to result in downregulation of pcpA expression (19). The antibody response elicited by recombinant PcpA vaccination has been shown to provide protection against systemic infection (18) but not against colonization (21) in mice. However, we have shown that commensal NP colonization of children results in production of mucosal and serum antibodies (16,22,23), strongly suggesting that expression of PcpA occurs in the NP of children, unlike mice.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…PcpA is under the control of a manganese (Mn)-dependent regulator, PsaR, and the Mn concentration in the NP of mice has been shown to result in downregulation of pcpA expression (19). The antibody response elicited by recombinant PcpA vaccination has been shown to provide protection against systemic infection (18) but not against colonization (21) in mice. However, we have shown that commensal NP colonization of children results in production of mucosal and serum antibodies (16,22,23), strongly suggesting that expression of PcpA occurs in the NP of children, unlike mice.…”
mentioning
confidence: 99%
“…The pcpA gene has been shown to be conserved among 25 different strains examined (18), and PcpA protein is surface exposed (18). PcpA is not required for NP colonization of the mouse (18,19) but is indispensable for murine lung infection (20). PcpA is under the control of a manganese (Mn)-dependent regulator, PsaR, and the Mn concentration in the NP of mice has been shown to result in downregulation of pcpA expression (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genome of the R6 strain does not have CbpI and CbpJ (8). Some of the CBPs, including PspA, PspC, and PcpA, have been described to be important virulence factors (7,(11)(12)(13), and PspA has been shown to be the major protein among the CBPs (14,15).…”
mentioning
confidence: 99%
“…Both procedures have the advantage that they would be expected to also elute some of the other CBPs, many of which have been shown to be virulence factors for pneumococci that are capable of eliciting measurable protection against colonization and/or invasive disease in mice (12,29). The purpose of these studies is to confirm some of the earlier work and to do the studies on a somewhat larger scale to determine whether it is possible and desirable to attempt to use one of these approaches to produce a pneumococcal vaccine.…”
mentioning
confidence: 99%